Auto‐calibration of a projector–camera stereo system for projection mapping. Issue 8 (11th August 2016) - Deglint, Jason; Cameron, Andrew; Scharfenberger, Christian; Sekkati, Hicham; Lamm, Mark; Wong, Alexander; Clausi, David A.
Abstract: Standard camera and projector calibration techniques use a checkerboard that is manually shown at different poses to determine the calibration parameters. Furthermore, when image geometric correction must be performed on a three‐dimensional (3D) surface, such as projection mapping, the surface geometry must be determined. Camera calibration and 3D surface estimation can be costly, error prone, and time‐consuming when performed manually. To address this issue, we use an auto‐calibration technique that projects a series of Gray code structured light patterns. These patterns are captured by the camera to build a dense pixel correspondence between the projector and camera, which are used to calibrate the stereo system using an objective function, which embeds the calibration parameters together with the undistorted points. Minimization is carried out by a greedy algorithm that minimizes the cost at each iteration with respect to both calibration parameters and noisy image points. We test the auto‐calibration on different scenes and show that the results closely match a manual calibration of the system. We show that this technique can be used to build a 3D model of the scene, which in turn with the dense pixel correspondence can be used for geometric screen correction on any arbitrary surface. Abstract : Auto‐calibration of a projector–camera system is carried out by a greedy algorithm that minimizes cost at each iteration with respect to both calibration parameters and noisy image points. Results closely match a manual calibration of the system. This technique is used to build a three‐dimensional model of a scene, and with the dense pixel correspondence, used for geometric screen correction.